Energy use patterns in German manufacturing since 2003 - Kathrine von Graevenitz; Elisa Rottner (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
The manufacturing sector accounts for a substantial share of German GDP, employment and carbon emissions. Therefore, the manufacturing sector's energy use and carbon emissions are of crucial importance for reaching Germany's climate goals. In this paper, we analyse energy use patterns in German manufacturing between 2003 and 2014, using rich administrative micro-data. We find that although the manufacturing sector has been faced with rising energy costs as a share of total costs, energy use has not declined except briefly during the economic crisis. We also find that energy intensity in the manufacturing sector has not decreased substantially. In contrast, carbon intensity has fallen slightly between 2003 and 2014. This can be attributed to changes in the fuel mix.
Keywords: D22; L60; Q41; 330; Energy use; Fuel mix; Energy intensity; Carbon emissions; Manufacturing